2018
DOI: 10.1038/mi.2017.67
|View full text |Cite
|
Sign up to set email alerts
|

PO and ID BCG vaccination in humans induce distinct mucosal and systemic immune responses and CD4+ T cell transcriptomal molecular signatures

Abstract: Protective efficacy of Bacillus Calmette-Guérin (BCG) may be affected by the methods and routes of vaccine administration. We have studied the safety and immunogenicity of oral (PO) and/or intradermal (ID) administration of BCG in healthy human subjects No major safety concerns were detected in the 68 healthy adults vaccinated with PO and/or ID BCG. Although both PO and ID BCG could induce systemic Th1 responses capable of IFN-γ production, ID BCG more strongly induced systemic Th1 responses. In contrast, stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 21 publications
0
39
0
Order By: Relevance
“…It is interesting to note that this particular substrain of BCG carries a unique RD16 region, which has been associated with its safety profile when delivered orally [72]. The oral vs intradermal administration of BCG Danish was also investigated in a small-scale trial in humans with no detectable adverse effects [4]. Although intradermal BCG induced stronger immune responses in the blood, oral BCG resulted in stronger mucosal responses in BAL and secretory IgA in nasal washes and tears.…”
Section: Bcg and Attenuated Whole-cell Live Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is interesting to note that this particular substrain of BCG carries a unique RD16 region, which has been associated with its safety profile when delivered orally [72]. The oral vs intradermal administration of BCG Danish was also investigated in a small-scale trial in humans with no detectable adverse effects [4]. Although intradermal BCG induced stronger immune responses in the blood, oral BCG resulted in stronger mucosal responses in BAL and secretory IgA in nasal washes and tears.…”
Section: Bcg and Attenuated Whole-cell Live Vaccinesmentioning
confidence: 99%
“…Although intradermal BCG induced stronger immune responses in the blood, oral BCG resulted in stronger mucosal responses in BAL and secretory IgA in nasal washes and tears. Oral vaccine administration is an attractive route mainly due to the ease of administration resulting in improved compliance but also due to the ability to induce responses at distal mucosal sites [4]. However, developing an oral vaccine has its challenges as it needs to be robust enough to withstand the harsh acidic environment in the stomach and requires the inclusion of an adjuvant to reduce the risk of tolerance [74].…”
Section: Bcg and Attenuated Whole-cell Live Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although human BCG today is primarily administered through the intradermal route, oral BCG administration has a long history and was used in multiple controlled studies performed in the 1920s and 1930s; demonstrating significant protection against TB (Aronson & Dannenberg, ; Kerszturi, ). More recent studies showed that oral BCG administration induces mucosal immunity, with enhanced TB‐specific secretory IgA, T‐cell homing to restricted lung mucosal compartments and bronchoalveolar lavage recovery of these T‐cells, compared to intradermal vaccination (Hoft et al., ; Lai, Afkhami, Haddadi, Jeyanathan, & Xing, ). In studies using rhesus macaques, pulmonary mucosal BCG vaccination conferred enhanced protection compared to standard intradermal BCG (Verreck et al., ), and it seems preferable to match the route of vaccination and natural infection (Manjaly & McShane, ).…”
Section: Efficacy Of Oral Bcgmentioning
confidence: 99%
“…More recent studies have focused on studying the relationship between acutely activated CD4 + and CD8 + T cells after vaccination and during the subsequent convalescent phase. For example, a distinct transcriptional and molecular signature in CD4 + T cells was used to distinguish effector phase versus memory responses in BCG vaccinated individuals [26]. Greenough et al demonstrated that particular transcription factors (eomesodermin and T-bet) allowed the identification of CD8 + T cells that expanded rapidly during acute infectious mononucleosis and enabled the proliferation and transition of these cells to later differentiation stages in convalescence [27].…”
Section: Introductionmentioning
confidence: 99%